علم النحو والصرف آلة لفهم اللغة العربية (الدراسة التحليلية فى كتب النحو) - M. Abdul Ghofur (Al-Fusha : Arabic Language Education Journal, 2019)
This study aims to provide insight into the importance of nahwu and shorf knowledge in understanding Arabic, because both are science tools that must be learned when someone wants to learn Arabic. The existence of this research is expected to be able to provide understanding for readers so as not to prioritize nahwu and shorf knowledge. This research uses descriptive method with a qualitative approach. The research subjects and studies of this research are nahwu books. The results of this study are that the science of nahwu and shorf is very influential in understanding Arabic texts, because Arabic texts cannot be understood without first learning this science.